Discovery of Polyoxypregnane Derivatives From Aspidopterys obcordata With Their Potential Antitumor Activity - Guo, Hong-Wei; Tian, Yun-Gang; Liu, Yi-Han; Huang, Jia; Wang, Jian-Xia; Long, Hua; Wei, Hua (Frontiers in Chemistry, 2022)
The bioassay-guided phytochemical study of an ethnic medicinal plant Aspidopterys obcorda ta Hemsl. var. obcordata results in the isolation of eight new polyoxypregnane derivatives, named aspidatasides A–H (1–8), along with ten known analogs (9–18). The series polyoxypregnane derivatives were screened for their cytoxic activity against HL-60 cells, and compound 2 showed the highest potency with an IC50 8.03 μM. Preliminary structure–activity relationship studies displayed that the sugar chain and double bond could notably impact their biological activity.